I'd like to solve the following integral:

$I = \int_0^\infty J_0(at) J_1(bt) e^{-t} dt\ $

where $J_n$ is an $n^{th}$ order Bessel Function of the First Kind and $a$ and $b$ are both positive real constants.

Any information about this integral would be useful.


I've included two relations specific to $0^{th}$ and $1^{st}$ order Bessel function that may be useful:

$ J_0(t)' = -J_1(t) $

$ J_1(t) = -J_{-1}(t) $

The following recursion relation may also be useful:

$ J_n(t)' = \frac{1}{2}\{J_{n-1}(t) - J_{n+1}(t) \} $

I've also found the following relation via integration by parts:

$ \int_0^\infty \{bJ_0(at) J_1(bt) + aJ_0(bt) J_1(at) \}e^{-t} dt\ = J_0^2(0) - \int_0^\infty J_0(at) J_0(bt) e^{-t} dt $


The integral does not admit a closed form, I am afraid. It is discussed in the vol. 2 of Bateman's "Higher Transcendental functions", section 7.7.3, formula 15, which gives $$ 2^{\mu + \nu} \alpha^{-\mu} \beta^{-\nu} \gamma^{\lambda + \mu+\nu} \Gamma\left(\nu+1\right) \int_0^\infty J_{\mu}(\alpha t) J_\nu(\beta t) \mathrm{e}^{-\gamma t} t^{\lambda -1} \mathrm{d} t = \sum_{m=0}^\infty \frac{\Gamma\left(2m+\lambda+\mu+\nu\right)}{m! \Gamma(m+\mu+1)} \cdot {}_2F_1\left(-m,-m-\mu; \nu+1; \frac{\beta^2}{\alpha^2}\right) \left( -\frac{\alpha^2}{4 \gamma^2} \right)^m $$ In your case, $\lambda = 1$, $\mu=0$, $\nu=1$, $\gamma=1$: $$ \frac{2}{\beta} \int_0^\infty J_0(\alpha t) J_1(\beta t) \mathrm{e}^{-t} \mathrm{d}t = \sum_{m=0}^\infty \frac{\Gamma\left(2m+2\right)}{m! \Gamma(m+1)} \cdot {}_2F_1\left(-m,-m; 2; \frac{\beta^2}{\alpha^2}\right) \left( -\frac{\alpha^2}{4} \right)^m $$

By expanding the Bessel function $J_1(b t)$ in its defining series and integrating term-wise we can find other series representations: $$ \int_0^\infty J_0(a t) J_1(b t) \mathrm{e}^{-t} \mathrm{d}t = \frac{b}{2} \sum_{m=0}^\infty \binom{2m+1}{m} \frac{\left(-\frac{b^2}{4}\right)^m}{(1+a^2)^{2m+3/2}} \cdot {}_2F_1\left(-m, -m-\frac{1}{2}; 1; -a^2\right) $$ where, additionally, the Euler's transformation of the Gauss' hypergeometric function had been used.


Unfortunately, I do not believe there is a simple closed form for this integral. One way forward, if you can call it that, is to express the integral as a series. For example, note that the Laplace Transform of $f(t) = J_0(a t)$ is

$$\hat{f}(s) = (s^2+a^2)^{-1/2}$$

Also note that Laplace transforms turn multiplication into differentiation as follows:

$$\int_0^{\infty} dt \: t^m \, f(t) e^{-s t} = (-1)^m \frac{\partial^m}{\partial s^m} \hat{f}(s)$$

Then using the Maclurin series for $J_1(b t)$:

$$J_1(b t) = \sum_{k=0}^{\infty} \frac{(-1)^k}{k!\,(k+1)!} \left ( \frac{b t}{2}\right )^{2 k+1}$$

we get the following expression for the integral:

$$\int_0^{\infty} dt \: J_0(a t) J_1(b t) e^{-t} = -\sum_{k=0}^{\infty} \frac{(-1)^k}{k!\,(k+1)!} \left ( \frac{b}{2}\right )^{2 k+1} \left [\frac{\partial^{2 k+1}}{\partial s^{2 k+1}} (s^2+a^2)^{-1/2} \right]_{s=1}$$


$\int_0^\infty J_0(at)J_1(bt)e^{-t}~dt$






$=\dfrac{b}{2}F_4\left(1,\dfrac{3}{2};1,2;-a^2,-b^2\right)$ (according to https://en.wikipedia.org/wiki/Appell_series#Definitions)


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.